The Small Bowel: An Imaging Guide - Twomey, Maria; Moloney, Fiachra; James, Karl; Sammon, Jennifer; O' Neill, Siobhan; J. O' Connor, Owen; M. Maher, Michael (Current Medical Imaging, 2017)
Background: This article reviews the latest radiological advances in the evaluation of small bowel disease. MRI and CT have been optimized in recent years for small bowel imaging including the development of enteric agents to distend the bowel, multiplanar thin-section imaging, advanced imaging applications, and radiation dose optimization techniques. Discussion: MR enterography, with the absence of ionizing radiation exposure, excellent tissue contrast, ultrafast breath-holding pulse sequences, and the ability to perform real-time functional imaging, has become the first-line imaging modality for the evaluation of the majority of small bowel disorders. Advanced MR applications including diffusion-weighted imaging, dynamic contrast-enhanced MRI, and motility imaging are becoming central in the imaging evaluation of small bowel disease. Conclusion: CT enterography is the preferred modality in patients with known or suspected inflammatory bowel disease in the acute setting to assess for extra-luminal complications. The enteroclysis technique is of use in selected cases in which adequate small bowel distention is not achieved with oral enteral contrast administration. Capsule endoscopy is reserved for patients in whom the clinical suspicion of small bowel disease remains high despite negative evaluations with endoscopy and imaging.
Keywords: Small bowel